2016
DOI: 10.1016/j.compbiomed.2016.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Generic feature learning for wireless capsule endoscopy analysis

Abstract: The interpretation and analysis of wireless capsule endoscopy (WCE) recordings is a complex task which requires sophisticated computer aided decision (CAD) systems to help physicians with video screening and, finally, with the diagnosis. Most CAD systems used in capsule endoscopy share a common system design, but use very different image and video representations. As a result, each time a new clinical application of WCE appears, a new CAD system has to be designed from the scratch. This makes the design of new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(62 citation statements)
references
References 44 publications
1
60
0
1
Order By: Relevance
“…The review presented only Zhou's study which has achieved a sensitivity and specificity of 100%. Seguí et al in (Seguí et al, 2016) presented a generic feature descriptor for the classification of video capsule endoscopy images. In order to build the system they created a large database containing only color images, designed a CNN architecture and performed an exhaustive validation of the proposed method.…”
Section: Ai Techniquesmentioning
confidence: 99%
“…The review presented only Zhou's study which has achieved a sensitivity and specificity of 100%. Seguí et al in (Seguí et al, 2016) presented a generic feature descriptor for the classification of video capsule endoscopy images. In order to build the system they created a large database containing only color images, designed a CNN architecture and performed an exhaustive validation of the proposed method.…”
Section: Ai Techniquesmentioning
confidence: 99%
“…A method using superpixel segmentation and naive Bayes classifier for bleeding frames detection was recently proposed in [43]. In [23,41,51], systems for small intestine motility characterization and bleeding detection, based on deep convolutional neural networks were introduced. The CE scores to assess small-bowel inflammatory activity in Crohn's disease were evaluated in [37].…”
Section: Related Workmentioning
confidence: 99%
“…polyps, ulcers, tumors and bleeding). Extensive reviews of these CAD systems can be found in [3,4,9]. Rapid Reader commercial software has been one of the most used diagnostic support tool since it provides, amongst other tools, the Suspected Blood Indicator (SBI), which identifies frames with possible red lesions in the gastrointestinal (GI) tract, based on color.…”
Section: Introductionmentioning
confidence: 99%
“…Computational methods for automatic image processing and analysis, such as smoothing filters, noise removal, contour detection or segmentation, can be used to facilitate the detection of anomalies/pathologies and to homogenize the response between different clinicians. Since 2012, Convolutional Neural Network (CNN), commonly known as "deep learning", started to present significantly better results than previous methods, automatically extracting characteristics from data and thus supporting new developments in CAD systems [9]. In this paper, an evaluation of deep learning U-Net architecture is presented for detecting and segmenting red lesions in the small bowel.…”
Section: Introductionmentioning
confidence: 99%